Assessment of Fetal Rhesus D and Gender with Cell-Free DNA and Exosomes from Maternal Blood - Yasa, Busra; Sahin, Orhan; Ocut, Elif; Seven, Mehmet; Sozer, Selcuk (SPRINGER HEIDELBERG, 2021)
The detection of fetal cell-free DNA (cfDNA) from maternal plasma has enabled the development of essential techniques in prenatal diagnosis during recent years. Extracellular vesicles including exosomes were determined to carry fetal DNA fragments. Considering the known difficulties during isolation and stability of cfDNA, exosomes might provide a new opportunity for prenatal diagnosis and screening. In this study, comparison of cfDNA and exosome DNA (exoDNA) for predicting the fetal sex and Rhesus D (RHD) genotype was performed by using real-time polymerase chain reaction with simultaneous amplification of sequences ofSRYandRHDgenes. Fetal sex andRHDwere determined in 100 and 81 RHD-negative pregnant women with cfDNA and exoDNA, respectively. The gestation ages of pregnant women were between 9 and 40 weeks. The results were compared with the neonatal phenotype for gender and a serological test for RHD. The cfDNA revealed 95.75% sensitivity and 100% specificity inRHDpositivity and 100% sensitivity and 95.45% specificity inSRYpositivity. Cohen's agreement coefficient in the Kappa test ranged from 0.8 to 1.0 (P < 0.00001). Although the exoDNA failed to amplify 16 cases, the remaining 65 cases revealed a true estimate for both fetalRHDandSRYgenes with 100% sensitivity and specificity. Successful application of exoDNA and cfDNA with real-time PCR for fetal genotyping enables this technique to be applied in the assessment of fetal RHD and gender during pregnancy, allowing initiation of early treatment methods and avoiding unnecessary interventions and cost.
Keywords: Cell-free DNA; Exosome; RHD; SRY; Fetal genotyping; PLASMA; TIME; Obstetrics & Gynecology; Reproductive Biology